Enhancing the functional properties of fish gelatin mats by dual encapsulation of essential oils in β-cyclodextrins/fish gelatin matrix via coaxial electrospinning - Mahmood, Kaiser; Kamilah, Hanisah; A Karim, Alias; Ariffin, Fazilah (Elsevier, 2023)
In this study, three EOs, namely cinnamaldehyde (CEO), limonene (LEO) and eugenol (EEO), together with ²-cyclodextrins (²CD) were encapsulated in the core of nanofibers via coaxial electrospinning to improve the functional properties of fish gelatin mat. The successful fabrication of nanofibers was verified by transmission electron microscopy (TEM) and an average fiber diameter of 251“378 nm was observed by scanning electron microscopy (SEM). Attenuated Fourier-transform infrared (ATR-FTIR) indicated a physical type of interaction between gelatin and EOs. Melting temperature (Tm) of nanofiber mats was improved with the incorporation of EOs-²CD while reduced mechanical strength was noticed. The encapsulation efficiency (EE) of EOs in nanofiber mats ranged from 69.7 to 93.2. A significantly enhanced antioxidant activity was noticed for nanofiber mats as evaluated through 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assay. Similarly, nanofiber mats presented strong antifungal activity when tested against Aspergillus niger. The developed nanofibers provided decent functional stability for 60 days by preserving the activity of dually encapsulated EOs. Finally, the nanofiber mats offered good control against the microbial spoilage of wheat bread stored for 10 days at ambient conditions. Thus, the developed nanofiber mats could be suitable for potential application as active packaging for low-to-intermediate moisture foods.